Effect of Foreign Direct Investment, Energy Consumption and Unemployment on Income Distribution in Malaysia - Rinashafika Redzuan; J.S Keshminde; Soo-Cheng Chuah; Maryam Jameelah Mohd Hashim (Information Management and Business Review, 2024)
The paper analyses the relationships between Foreign Direct Investment (FDI), Energy Consumption, Unemployment, and their effects on Income Distribution in Malaysia from 1990-2022. Despite economic growth, Malaysia faces income inequality, especially among ethnic groups. The study uses ARDL regression to find that FDI promotes income distribution by creating jobs and facilitating technology transfer. Increased energy availability boosts industrial production, which is crucial for equitable income distribution. High unemployment, particularly among graduates, exacerbates income inequality. Government initiatives aim to address unemployment through skills enhancement and entrepreneurship. The study concludes that FDI and energy consumption positively influence income distribution, while unemployment has a negative impact. The findings are valuable for policymakers in fostering inclusive growth and equitable income distribution in Malaysia. As Malaysia is an export-oriented country, these insights can lead to impactful improvements in the export sector, further boosting employment opportunities and economic resilience.